Aggressive Cardiac Involvement in Systemic Lupus Erythematosus: A Case Report and a Comprehensive Literature Review - Reza Ashrafi; Pankaj Garg; Ewan McKay; John Gosney; Som Chuah; Gershan Davis (Cardiology Research and Practice)
Background. We present the case of a 35-year-old gentleman who presented with an aggressive cardiomyopathy with normal coronary arteries. He was later diagnosed with systemic lupus-related cardiomyopathy. Methods. We undertook an extensive review of the literature regarding cardiac manifestations of lupus and used over 100 journals to identify the key points in pathology, diagnosis, and treatment. Results. We have shown that cardiac lupus can be rapidly progressive and, unless treated early, can have severe consequences. The predominant pathologies are immune complex and accelerated atherosclerosis drive. Treatment comprised of high-level immunosuppression.